Reproducibility and Accuracy of MR Imaging of the Brain after Severe Birth Asphyxia - Jouvet, Phillipe; Cowan, Francis M.; Cox, Philip; Lazda, Edward; Rutherford, Mary A.; Wigglesworth, Jonathan; Mehmet, Huseyin; Edwards, A. David (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: MR imaging of the brain can be used to detect cerebral damage after suspected hypoxic-ischemic injury. This study examines the reproducibility and accuracy of MR imaging soon after severe birth asphyxia.METHODS: During a 48-month period, full-term newborn neonates, who died within the first week as a result of severe hypoxic ischemic encephalopathy, were included in the study if they had undergone early (<5 days old) MR imaging and postmortem neuropathologic studies. Two trained observers assessed reproducibility by examining multiple brain regions independently with current criteria and then defining and applying improved criteria. Accuracy of MR findings was tested by comparing the brain regions about which the two imaging raters agreed to those regions about which the two pathologists agreed.RESULTS: Eight neonates, with a median gestational age of 40 weeks (range, 38-40 weeks) and who suffered severe birth asphyxia, were included in the study. In the reproducibility study, MR imaging agreement was moderate when current criteria were used (k = .44). Using the improved criteria, agreement increased considerably (k = .62). Much of this improvement was due to limiting the analyses to the posterior limb of the internal capsule, thalamus, parietal cortex, hippocampus, and medulla. The posterior limb of the internal capsule was the most reliable region analyzed. MR imaging agreement was similar to that achieved by two experienced pathologists reviewing the histologic sections (k = .66). In the accuracy study, MR imaging abnormality was predictive of pathologic abnormality with a sensitivity of .79 and a positive predictive value of 1.0. The predictive value of a single MR imaging abnormality was .79 (95% confidence interval, .61-.96).CONCLUSION: Criteria that provide substantial reproducibility and accuracy for the interpretation of MR imaging findings very early after birth asphyxia can be derived.